A Cycle of Wind-Driven Canyon Upwelling and Downwelling at Wilmington Canyon and the Evolution of Canyon-Upwelled Dense Water on the MAB Shelf - Wang, Haixing; Gong, Donglai; Friedrichs, Marjorie A. M.; Harris, Courtney K.; Miles, Travis; Yu, Hao-Cheng; Zhang, Yinglong (Frontiers in Marine Science, 2022)
Submarine canyons provide a conduit for shelf-slope exchange via topographically induced processes such as upwelling and downwelling. These processes in the Wilmington Canyon, located along the shelf-break of the Mid-Atlantic Bight (MAB), have not been previously studied, and the associated hydrographic variability inside the canyon and on the adjacent shelf are largely unknown. Observations from an underwater glider deployed in Wilmington Canyon (February 27 - March 8, 2016), along with wind and satellite altimetry data, showed evidence for a wind-driven canyon upwelling event followed by a subsequent downwelling event. Next, a numerical model of the MAB was developed to more fully represent these two events. Modeled results showed that under upwelling-favorable winds during February 25 - March 3, sea level increased seaward, shelf currents flowed northeastward, and canyon upwelling developed. Then under downwelling-favorable winds during March 4-7, sea level increased landward, shelf currents flowed southwestward, and canyon downwelling developed. Modeling experiments showed that canyon upwelling and downwelling were sub-tidal processes driven by winds and pressure gradients (associated with SSH gradients), and they would occur with or without tidal forcing. During the upwelling period, slope water originating from 150-215 m depths within the canyon (75 m below the canyon rim), was advected onto the shelf, forming a cold and dense canyon-upwelled slope-originated overflow water at the bottom of the outer shelf (75-150 m isobaths). The dense overflow current flowed was directed northeastward and expanded in the cross-shelf direction. It was 5-20 km wide and 10-30 m thick. The estimated volume of the plume overflow water exceeded 6×10^9 m^3 at peak. The density front at the shoreward side of the dense overflow water caused a subsurface baroclinic frontal jet, which flowed northeastward and along-shelf with maximum speed exceeding 0.5 m/s. In the ensuing downwelling event, a portion of the previously upwelled dense water was advected back to the canyon, and then flowed down-slope in the upper canyon in 0.3 m/s bottom-intensified currents. Dynamical investigation of the overflow current showed that its evolution was governed by unbalanced horizontal pressure gradient force in the cross-shelf direction and that the current was geostrophic.